2019
DOI: 10.36348/sjmps.2019.v05i10.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses’ Knowledge and Practice for Prevention of Infection in Burn Patients

Abstract: Objective: To assess nurses' knowledge and evaluate their practice for prevention of infection among burn patients, also to suggest guidelines especially of nursing practice for prevention of infection in burn patients. Study Design: A descriptive cross sectional study. Place and Duration: Six months, from April 2017 to Sep 2017, in burn units of 03 selected hospitals of Lahore. Methods: The study included all nurses who were providing care to burn patients (N=48). Nurses' knowledge was assessed by using a sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
2
1
Order By: Relevance
“…the results of wound culture. 25 In our study, in parallel with the literature, it was found that the participants had low scores in terms of attitudes before and after the training in terms of interpreting the time to take a wound culture in wound infection, which microorganisms can be found as a result of wound culture. The attitude of healthcare professionals is an important quality that helps to understand how issues or processes in clinical care are perceived and to decide what is appropriate for the health of patients.…”
Section: Nurses' Attitudes Towards Wound Infection and Wound Culturesupporting
confidence: 78%
“…the results of wound culture. 25 In our study, in parallel with the literature, it was found that the participants had low scores in terms of attitudes before and after the training in terms of interpreting the time to take a wound culture in wound infection, which microorganisms can be found as a result of wound culture. The attitude of healthcare professionals is an important quality that helps to understand how issues or processes in clinical care are perceived and to decide what is appropriate for the health of patients.…”
Section: Nurses' Attitudes Towards Wound Infection and Wound Culturesupporting
confidence: 78%
“…However, 73% of them had satisfactory knowledge regarding complications dressing [15]. Also, it is higher than that found by another study in Egypt [16] and Saudi Arabia [10]. This might be because most nurses in this study were diploma degree holders and had a deeper knowledge base on their long experience in burn units which draw in such areas as clinical practice and critical thinking.…”
Section: Discussioncontrasting
confidence: 57%
“…The management and maintenance of burned patients need an entire body of knowledge and skills from a responsible multidisciplinary team. Thus, capable nurses should be well-practised, and specific infection control guidelines should be developed for that purpose, especially to prevent/control hospital-acquired infection [10]. Therefore, the current study aimed to assess nurses' knowledge and practice regarding burn wound dressing in Sulaimaniyah City, Iraq.…”
Section: Introductionmentioning
confidence: 99%
“…The discoveries of the present examination uncovered medical attendants' low degree of information and practices. Thus, health care settings are required to compose propelled instructional courses and to create unit explicit clinical rules and conventions (Buksh, Ghani, Amir, Asmat, & Ashraf, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%